A Small-Sized Locating Message for Cooperative Localization under Communication Constraint. (29th April 2016) - Wang, Leigang; Zhang, Tao; Liang, Rongjian
When one agent simultaneously measures multiple teammates in cooperative localization, how to share these relative measurements with low-cost communication is interesting. In this chapter, different communication requirements for sharing absolute measurement and relative measurement are analyzed under extended Kalman filtering, whereby we develop an algorithm to convert multiple relative measurements into one virtual absolute measurement. By this, less number of elements are required to be transmitted across the agents. The utilization of multi-relative measurements is changed to the mode of one round communication from conventional mode where the measurements are processed and broadcast one by one. Simulation results demonstrate that, using the virtual absolute measurement, the almost equal localization performance with real relative measurements is obtained.